Surfactant lung lavage in neonatal meconium aspiration syndrome as a life-saving respiratory strategy: literature review and a case report - A. V. Mostovoi; A. L. Karpova; I. V. Popov; L. A. Anikeeva; N. Yu. Karpov (Акушерство, гинекология и репродукция)
Here, we review the latest available studies on using surfactant lavage in newborns with severe manifestations of meconium aspiration syndrome (MAS), illustrated by a representative clinical case. Meconium-stained amniotic fluid may be found in 8-20 % of all births, with the incidence reaching 23-52 % after a full 42 weeks of gestation. From 2 to 9 % of newborns with meconium-stained amniotic fluid subsequently develop MAS clinical signs. About a third of newborns with MAS require tracheal intubation and mechanical ventilation. MAS-related mortality rate due to severe injuries of the lung parenchyma and the development of pulmonary hypertension, can exceed 20 %. Other complications, including air leak syndrome (ALS), occur in 10-30 % of children with MAS. Surfactant lavage may be one of the clinical tools that avoids extracorporeal membrane oxygenation (ECMO) in severe MAS cases. This clinical observation is also of interest because a mature, even post-term newborn with MAS subsequently developed a typical bronchopulmonary dysplasia (BPD), which required proper treatment.